2019
DOI: 10.1097/tp.0000000000002639
|View full text |Cite
|
Sign up to set email alerts
|

Use of Eculizumab for Active Antibody-mediated Rejection That Occurs Early Post–kidney Transplantation: A Consecutive Series of 15 Cases

Abstract: Background. Active antibody-mediated rejection (AMR) that occurs during the amnestic response within the first month posttransplant is a rare but devastating cause of early allograft loss after kidney transplant. Prior reports of eculizumab treatment for AMR have been in heterogeneous patient groups needing salvage therapy or presenting at varied time points. We investigated the role of eculizumab as primary therapy for active AMR early posttransplant. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…In particular, much was initially learned from the series of Stegall et al in 2011 3 where 26 highly sensitized patients with positive crossmatches (by flow cytometry) were transplanted with an eculizumab‐based induction protocol. Compared with a historical control group, they found that the incidence of acute AMR was reduced in the eculizumab group (7.7% vs 41.2%) 3,12,20 . All patient had thymoglobulin induction, and the majority of patients (69%) had pre‐transplant plasmapheresis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, much was initially learned from the series of Stegall et al in 2011 3 where 26 highly sensitized patients with positive crossmatches (by flow cytometry) were transplanted with an eculizumab‐based induction protocol. Compared with a historical control group, they found that the incidence of acute AMR was reduced in the eculizumab group (7.7% vs 41.2%) 3,12,20 . All patient had thymoglobulin induction, and the majority of patients (69%) had pre‐transplant plasmapheresis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a recent retrospective analysis from the Mayo Clinic, 15 kidney allotransplant recipients were identified with early acute AMR within the first 30 days post‐transplant, all having an abrupt increase in donor‐specific antibodies (DSA) with rapid allograft dysfunction. Prompt eculizumab treatment, together with plasmapheresis in most cases, was found safe and effective for this type of early acute and active AMR, indicating that targeting C5 with immediate blockade of the terminal pathway of complement may be useful to prevent graft loss 12 …”
Section: Introductionmentioning
confidence: 99%
“…137 A case series (N = 15) of early active ABMR treated with eculizumab plus PLEX as primary (rather than salvage) therapy also showed an impressive increase of median eGFR with no graft loss at minimum of 12-months follow-up. 138 The development of complement-targeting therapies is a fast evolving field and there are many new agents, which will require rigorous testing in transplantation (e.g., ravalizumab or anti-C1s antibody BIVV009). 139,140 Although the current evidence suggests efficacy for complement inhibitors in the treatment of ABMR, combination with DSA-reducing strategies to mitigate other non-complement-related DSA effector functions will likely be required.…”
Section: Novel Strategies To Target Alloantibody Effector Functionmentioning
confidence: 99%
“…Additionally, the effectiveness of anticomplement drugs for AMR treatment has also been reported. The administration of eculizumab, a humanized anti-C5 monoclonal antibody against active AMR, in the early stage after transplantation generally improved the pathological findings and function of transplanted grafts [ 140 ]. Eculizumab administration was also effective in preventing AMR development after transplantation, even in pre-DSA–positive cases of living kidney transplantation [ 141 ].…”
Section: Significance Of Complement Activation In the Field Of Tramentioning
confidence: 99%